Optimization of Double Hole Composite Plate on the Floater Compartment of Amphibious Aircraft Using Taguchi Method - Nurrohmad, Abian; Antares, Quincy; Nuranto, Awang Rahmadi; Nugroho, Afid (Badan Kebijakan Transportasi, Kementerian Perhubungan, 2023)
A floater or pontoon is one of the most important components of amphibious aircraft to assist the take-off and landing operation. The inner structure of the floater consists of compartments to carry some payload and to reinforce the structural strength due to water and aerodynamic load that occurred during the aircraft operation. The composite material is chosen instead of metal to reduce the weight of the floater. One of the problems on the composite panel is the existence of some holes due to joint with another part or also to minimize its weight. In this study, the optimization of the composite plate with the existence of a double hole is done using the Taguchi Method. The objective of this optimization is to minimize the stress that happens due to the tensile load. The Finite Element Method is used to calculate the maximum stress and stress distribution on the plate. Tsai-Hill failure criterion is used to make sure that the optimum design does not fail. This optimization considers open hole configuration, the ratio between diameter, and hole distance, as well as the fiber orientation as the control factors. The Taguchi L9 Orthogonal Array is used to make 9 design variations from 3 control factors and 3 levels. This process also considers the thickness of the lamina and material strength as noise factors. The optimization process results in the optimum composite design as follows: 1st double hole configuration (in line with the load direction), the ratio between diameter and hole distance is 0.5, and the fiber direction is [0/90/45/-45]s. The maximum in-plane stress of the optimum design is 39.56 MPa with the Tsai-Hill value is 0.23, so the design does not fail. This optimum configuration of the composite plate can be used to make design considerations for an amphibious aircraft floater compartment.